Asian noodles : science, technology, and processing - Hou, Gary G. (John Wiley & Sons, 2010)
In Asian Noodles: Science, Technology and Processing, international experts review the current knowledge and offer comprehensive cutting-edge coverage on Asian noodles unmatchable in any publication. The authors cover an array of topics including breeding for noodle wheat, noodle flour milling, noodle flour quality control and analysis, noodle processing, sensory and instrumental measurements of noodle quality, the effects of wheat factors on noodle quality, packaging and storage, nutritional fortification of noodle products, noodle flavor seasoning, and noodle plant setup and management.